2002
DOI: 10.1046/j.1469-8137.2002.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction and offspring competitiveness of Senna obtusifolia are influenced by nutrient availability

Abstract: Summary• Senna obtusifolia (sicklepod) is a troublesome weed in many agronomic cropping systems in the southeastern USA with varying fertility regimes. This series of experiments was initiated to determine the impact of nutrient availability on reproductive output and maternal effects.• Experiments were conducted with plants growing in soil in growth chambers for 120 d. Offspring growth was evaluated in hydroponics.• Plants grown under higher nutrient conditions had greater reproductive biomass, number of seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 57 publications
(98 reference statements)
4
31
0
1
Order By: Relevance
“…The fertility of the maternal growth environment can lead to differences in seed nutrient content (Fenner, 1992;Wulff, 1995). It is logical to think that the expression of maternal effects in offspring and offspring competitiveness (Stratton, 1989;Tungate et al, 2002;Wulff et al, 1994) could be associated with responses like those observed in these experiments with soybean.…”
Section: Larger-scale Implicationsmentioning
confidence: 87%
See 1 more Smart Citation
“…The fertility of the maternal growth environment can lead to differences in seed nutrient content (Fenner, 1992;Wulff, 1995). It is logical to think that the expression of maternal effects in offspring and offspring competitiveness (Stratton, 1989;Tungate et al, 2002;Wulff et al, 1994) could be associated with responses like those observed in these experiments with soybean.…”
Section: Larger-scale Implicationsmentioning
confidence: 87%
“…Seed reserves may be the primary and, in some cases, the only source of N that can drive growth processes. A key regulatory role for seed N was implied by studies showing that higher seed nutrition was associated with increased seedling vigor when fertility was low (Bulsani and Warner, 1980;Hara and Toriyama, 1998;Nedel et al, 1996;Parrish and Bazzaz 1985;Ries, 1971;Tungate et al, 2002;Welch, 1999). There has not been, however, a detailed study of the relationship between the seed N resource level and physiological responses of seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated different aspects of inter-population variation in seed production and seed mass, including climatic factors (Murray et al 2004;Poncet et al 2009), altitudinal gradients (Totland and Birks 1996;Pluess et al 2005), latitudinal variation (Winn and Gross 1993;Garcia et al 2000;Moles and Westoby 2003;Murray et al 2004;Moles et al 2007;De Frenne et al 2009), soil fertility (Wolfe 1995;Tungate et al 2002) and differences in habitat type (Endels et al 2004;Goulart et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the Alps provide an interesting land use gradient from extensive to intensive grasslands to test plant and community functions. Studies addressing the effects of nutrient availability on seed production detected a positive relationship between them (Tungate et al 2002;Burkle and Irwin 2009), yet data continues to generate conflicting results which support a correlation between increased seed mass and soil nutrient levels. Breen and Richards (2008) found larger seeds were associated with increased soil nutrition, however, other studies detected no relationship (Wolfe 1995;Tungate et al 2002) between seed size and soil nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Hendrix (1984) determinó que las semillas grandes poseen mayor porcentaje de germinación, y en este sentido, los resultados obtenidos en este estudio no concuerdan del todo con el autor, pues el porcentaje de germinación se inclinó mayormente en las semillas pequeñas en dos de los tres tratamientos evaluados. Posiblemente esto se debe a que a mayor tamaño, mayor tiempo en germinar, como lo consideran Gomes et al (2001), Tungate et al (2002), Kikuzawa & Koyama (1999), Teketay & Granstrom (1997), Milberg et al (1996) y Harper et al (1970. Además de lo considerado por los autores anteriormente citados, es necesario tomar en cuenta que el tegumento de la semilla está constituido por tejido esponjoso que forma las cámaras de aire (Sánchez-Salas et al 2012) y por consecuencia, a menor tamaño de semilla, menor número de cámaras de aire, que inducirán la germinación en menor tiempo.…”
Section: Germinaciónunclassified